Adinugraha's Perspective Islam Economics In The Digital Era - Adinda Riski Amalia (STAIN Bengkalis, 2023)
In this digital era, information and communication technology allows wider access for all parties to be involved in economic activities. Examining more about the economy in the digital era is important for Muslim societies because the digital economy can be called an economic system that is developing rapidly and has a significant impact on economic activities around the world. Matters that need attention include compliance with Islamic economic principles in transactions that occur online, as well as security and privacy issues related to the use of information and communication technology in economic activities. The purpose of this study is to understand the concept of the digital economy, understand the values and norms of Islamic economics from the perspective of Hendri Hermawan Adinugraha, and the relevance of the digital economy to the values and norms of Islamic economics. This research is a literature study (literature review) with a descriptive qualitative approach. The research results obtained, the digital economy is an economic system that uses information and communication technology as a basis for carrying out economic activities. Islamic economic values and norms are the principles held by Muslim communities in carrying out economic activities, which are based on Islamic religious teachings. The relevance between the digital economy and Islamic economic values and norms lies in the ability of information and communication technology to support the implementation of these principles.